The Diseased Brain and the Failing Mind Dementia in Science, Medicine and Literature of the Long Twentieth Century - Zimmermann, Martina (Explorations in Science and Literature, 2020)
This book is available as open access through the Bloomsbury Open programme and is available on www.bloomsburycollections.com. It is funded by The Wellcome Trust. The Diseased Brain and the Failing Mind charts changing cultural understandings of dementia and alzheimer's disease in scientific and cultural texts across the 20th Century. Reading a range of texts from the US, UK, Europe and Japan, the book examines how the language of dementia - regarding the loss of identity, loss of agency, loss of self and life - is rooted in scientific discourse and expressed in popular and literary texts. Following changing scientific understandings of dementia, the book also demonstrates how cultural expressions of the experience and dementia have fed back into the way medical institutions have treated dementia patients. The book includes a glossary of scientific terms for non-specialist readers.